CD11a expression distinguishes infiltrating myeloid cells from plaque-associated microglia in Alzheimer’s Disease. - Shukla, Ankita K. (Glia, 2018)
Alzheimer’s Disease (AD) is the leading cause of age-related neurodegeneration and is characterized neuropathologically by the accumulation of insoluble beta-amyloid (Aß) peptides. In AD brains, plaque-associated myeloid (PAM) cells cluster around Aß plaques but fail to effectively clear Aß by phagocytosis. PAM cells were originally thought to be brain-resident microglia. However, several studies have also suggested that Aß-induced inflammation causes peripheral monocytes to enter the otherwise immune-privileged brain. The relationship between AD progression and inflammation in the brain remains ambiguous because microglia and monocyte-derived macrophages are extremely difficult to distinguish from one another in an inflamed brain. Whether PAM cells are microglia, peripheral macrophages, or a mixture of both remains unclear. CD11a is a component of the ß2 integrin LFA1. We have determined that CD11a is highly expressed on peripheral immune cells, including macrophages, but is not expressed by mouse microglia. These expression patterns remain consistent in LPS-treated inflamed mice, as well as in two mouse models of AD. Thus, CD11a can be used as a marker to distinguish murine microglia from infiltrating peripheral immune cells. Using CD11a, we show that PAM cells in AD transgenic brains are comprised entirely of microglia. We also demonstrate a novel Fluorescence-Assisted Quantification Technique (FAQT), which reveals a significant increase in T lymphocytes, especially in the brains of female AD mice. Our findings support the notion that microglia are the lead myeloid players in AD and that rejuvenating their phagocytic potential may be an important therapeutic strategy.